Banditry as seen in criminal canonical law - MAJCHRZAK, KATARZYNA (Prawo Kanoniczne, 2013)
The article touches upon the crime of banditry as seen in criminal canonical law. It depicts the way in which the crime of banditry was presented in the Code of Canonical Law both of 1917 and of 1983. The crime of banditry is committed by a person who steals another person’s property while resorting to or threatening to resort to violence or while bringing a person to the state of unconsciousness ordefenselessness.Banditry falls within intentional crimes intended to take another person’s property willfully in order to misappropriate it. The crime of banditry has always been treated as one of the heaviest crimes against property. In terms of its burden, the way the crime was committed is decisive, among others. Frequently this attack ends up in taking life of an assaulted person or in a serious damage to his or her body. In criminal canonical law the crime of banditry falls within mixti fori crimes which means that the perpetrator may be pursued and punished both by church and national authorities. The canonical judge while respecting the principle of natural law which says ne bis idem, is forced to take into account national criminal laws in his proceedings. Such reasoning is justified by CIC/1917 can. 2198, can. 1933 §3, can. 2223 §3 n. 2 and can. 2354 §1-2 and in CIC/1983 particularly can. 1344 n. 2 and can. 1399.